2015
DOI: 10.1007/s00392-015-0895-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and covariates of fear of death during myocardial infarction and its impact on prehospital delay: findings from the multicentre MEDEA Study

Abstract: FoD is experienced by a clinically meaningful minority of vulnerable STEMI patients and is strongly associated with shorter delay times in men but not in women. Patients' uses of emergency services play an important role in reducing the delay in male FoD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
3
24
1
Order By: Relevance
“…Our findings indicating higher levels of death anxiety in MI patients were consistent with previous studies 16, 17, 18, 19. While higher levels of anxiety predict for a heart attack according to literature, heart attack itself seems to be a predictor for higher levels of anxiety 20, 21.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings indicating higher levels of death anxiety in MI patients were consistent with previous studies 16, 17, 18, 19. While higher levels of anxiety predict for a heart attack according to literature, heart attack itself seems to be a predictor for higher levels of anxiety 20, 21.…”
Section: Discussionsupporting
confidence: 93%
“…While studies on MI’s association with anxiety levels are mostly focused on anxiety as a predictor for cardiac event,13, 14, 15 a few studies focused on anxiety levels during or after the course of MI 16, 17. Studies focusing specifically on death anxiety or fear of death are fewer 18, 19…”
Section: Discussionmentioning
confidence: 99%
“…We found no relationship between fear of death with age and gender, as in the MEDEA study [18], but it is in contradiction to one study in which women reported fear of death more frequently [17].…”
Section: Discussioncontrasting
confidence: 99%
“…Fear of death is often referred to as one of the main symptoms of ACS [16][17][18][19]; however, its magnitude and relevance are not fully determined. There is also scarce evidence on the predictors of fear of death in ACS patients.…”
Section: Introductionmentioning
confidence: 99%
“…An acute myocardial infarction (AMI) with its traumatizing and life threatening onset (4) may qualify as a condition where denial may serve as a prominent maladaptive coping mechanism (4-6). Indeed, some small exploratory studies, mainly performed over 10 years ago, provided a preliminary evidence that denial contributes to delayed adherence to effective cardiac treatment by disavowing of the diagnosis and by minimizing the perceived symptom burden and symptom severity (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%